The roots of f(x) = x^4-2x^3+5x^2-8x+4 have to be determined.

x^4-2x^3+5x^2-8x+4 = 0

=> x^4 - x^3 - x^3 + x^2 + 4x^2 - 4x - 4x + 4 = 0

=> x^3(x - 1) - x^2(x - 1) + 4x(x - 1) - 4(x - 1) = 0

=>...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The roots of f(x) = x^4-2x^3+5x^2-8x+4 have to be determined.

x^4-2x^3+5x^2-8x+4 = 0

=> x^4 - x^3 - x^3 + x^2 + 4x^2 - 4x - 4x + 4 = 0

=> x^3(x - 1) - x^2(x - 1) + 4x(x - 1) - 4(x - 1) = 0

=> (x^3 -x^2 + 4x - 4)(x - 1) = 0

=> (x^2(x - 1) + 4(x - 1))(x - 1) = 0

=> (x^2 + 4)(x - 1)^2 = 0

x - 1 = 0

=> x = 1

x^2 + 4 = 0

=> x = 2i and x = -2i

**The roots of f(x) = x^4 - 2x^3 + 5x^2 - 8x + 4 are 2i, -2i and 1.**